2022
DOI: 10.3389/feart.2022.907609
|View full text |Cite
|
Sign up to set email alerts
|

Application of Time Series Analysis to Estimate Drawdown From Multiple Well Fields

Abstract: In 2018–2020, meteorological droughts over Northwestern Europe caused severe declines in groundwater heads with significant damage to groundwater-dependent ecosystems and agriculture. The response of the groundwater system to different hydrological stresses is valuable information for decision-makers. In this paper, a reproducible, data-driven approach using open-source software is proposed to quantify the effects of different hydrological stresses on heads. A scripted workflow was developed using the open-sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The finding that for these five monitoring wells there are multiple model structures that perform almost equally well to simulate the heads, only came to light after this additional analysis. A multi-model approach, as for exam-ple is taken in Brakenhoff et al (2022) as well as in this study for the snow model, would have revealed this issue at an earlier stage and is therefore recommended for future studies. This way, additional criteria can be used to make a more informed decision and to determine which model is best and used for further analysis.…”
Section: Selecting Appropriate Model Structuresmentioning
confidence: 94%
See 2 more Smart Citations
“…The finding that for these five monitoring wells there are multiple model structures that perform almost equally well to simulate the heads, only came to light after this additional analysis. A multi-model approach, as for exam-ple is taken in Brakenhoff et al (2022) as well as in this study for the snow model, would have revealed this issue at an earlier stage and is therefore recommended for future studies. This way, additional criteria can be used to make a more informed decision and to determine which model is best and used for further analysis.…”
Section: Selecting Appropriate Model Structuresmentioning
confidence: 94%
“…( 9)). Such an approach has also been applied in other studies to determine if a stress is influencing the heads or not, for example for pumping wells (Collenteur et al, 2019;Brakenhoff et al, 2022). For five monitoring wells (Ermensee, Oberglatt, Poschiavo, Visp, and Wila), the parameter for the gain of the response to river stage changes (A riv ) was estimated at the upper boundary value of A riv = 1.…”
Section: Selecting Appropriate Model Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The shallow subsurface is characterized by a low-permeable phreatic layer, underlain by two aquifers separated by an aquitard. The groundwater is relatively shallow, with the depth to the water table varying between 0.8 and 4.2 m. For a more comprehensive understanding of the hydrological system, the reader is referred to the work of 7 .…”
Section: Data Descriptionmentioning
confidence: 99%
“…Our study focuses on leveraging ST-GNNs to predict groundwater levels in the Overbetuwe area, Netherlands. The selection of this area is driven by the availability of data 7 .…”
Section: Introductionmentioning
confidence: 99%